GERMINAÇÃO DE SEMENTES DE Piptadenia moniliformis Benth. SOB ESTRESSE HÍDRICO - Azerêdo, Gilvaneide Alves De; Paula, Rinaldo Cesar De; Valeri, Sérgio Valiengo (Universidade Federal de Santa Maria, 2016)
The period of germination and the establishment of seedlings are important factors for the survival of species, mainly in places where availability of water is limited, as in the Caatinga region. In this sense, the purpose of this research was to evaluate the effect of water stress on the germination of Piptadenia moniliformis Benth seeds. Three lots (L1, L2 e L3) were used, corresponding to the production years of 2006, 2007 and 2008, respectively. Before the germination test, the seeds were submitted to scarification in concentrated sulfur acid for 30 minutes. To induce water deficit, polyethyleneglicol (PEG 6000) was used, in the following osmotic potentials: - 0,3; -0,6; -0,9, -1,2 and -1,5 MPa and water (0 MPa) under the temperatures of 25 and 30 ºC. The features the experiment evaluated were: percentage of germination and of normal seedlings, germination speed index and the dry mass of seedlings. The germinating process of Piptadenia moniliformis Benth seeds is jeopardized from water potentials inferior to -0,6 MPa at 25 and 30 °C; water potentials equivalent or inferior to -1,2 MPa inhibit the formation of normal seedlings in both temperatures; the tolerance to water stress simulated with PEG 6000 is variable among seedling lots and germination temperatures.

O período de germinação e o estabelecimento de plântulas é um dos fatores mais importantes para a sobrevivência das espécies, principalmente nos locais em que a disponibilidade de água é limitada, como na região da Caatinga. Neste sentido, o objetivo deste trabalho foi avaliar o efeito do estresse hídrico sobre a germinação de sementes de Piptadenia moniliformis Benth. Foram utilizados três lotes (L1, L2 e L3), correspondentes aos anos de produção de 2006, 2007 e 2008, respectivamente. Antes do teste de germinação, as sementes foram escarificadas com ácido sulfúrico concentrado durante 30 minutos. Para induzir o deficit hídrico, foi utilizado o polietileno glicol (PEG 6000), nos seguintes potenciais osmóticos: - 0,3; -0,6; -0,9, -1,2 e -1,5 MPa e a água (0 MPa) sob as temperaturas de 25 e 30ºC. As características avaliadas foram: porcentagem de germinação e de plântulas normais, índice de velocidade de germinação e massa seca de plântulas. O processo germinativo de sementes de Piptadenia moniliformis Benth. é comprometido a partir de potenciais hídricos inferiores a -0,6 MPa a 25 e 30 °C; potenciais hídricos iguais ou inferiores a -1,2 MPa inibem a formação de plântulas normais nas duas temperaturas; a tolerância ao estresse hídrico simulado com PEG 6000 é variável entre lotes de sementes e temperaturas de germinação.
GERMINATION OF Piptadenia moniliformis Benth SEEDS UNDER WATER STRESS
Keywords: PEG; seedlings growth; Caatinga; PEG; crescimento de plântulas; Caatinga